The Times They Are a Changing (Or Are They?): Exploring the Impact of the Tenure Process on Racialized Faculty at a US and an Anglophone Caribbean Institution - Dianne Ramdeholl; Mervin Chisholm (Adult Education Research Conference, 2018)
This paper builds on two completed studies charting faculty perceptions of student evaluations in the tenure process in a US and Caribbean context offering recommendations for new faculty of color.
Keywords: adult education; critical race theory